2006
DOI: 10.1002/app.23876
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring of phase‐segregation structures in two‐soft‐segment urethane/urea polymer membranes

Abstract: The synthesis of two-soft-segment urethane/ urea polymeric membranes with various proportions of the two soft segments, poly(propylene oxide) and polybutadiene, yielded very distinct morphologies depending on the degree of phase segregation. The morphologies were identified with transmission electron microscopy. With a low concentration of polybutadiene, this soft segment segregated into ellipsoidal microdomains dispersed in a poly(propylene oxide) matrix. With an intermediate concentration of polybutadiene, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
0
7
0
2
Order By: Relevance
“…The initial composition and the inherent reaction path play the fundamental role for the final morphology. This is crucial for a tailored surface or morphology design and is particularly important for, e.g., membrane science 12,14,32. An extension of the present study with focus on stabilization of tailored morphologies would be of great interest since the morphology control and particularly morphology conservation is a basic requirement in membrane synthesis.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The initial composition and the inherent reaction path play the fundamental role for the final morphology. This is crucial for a tailored surface or morphology design and is particularly important for, e.g., membrane science 12,14,32. An extension of the present study with focus on stabilization of tailored morphologies would be of great interest since the morphology control and particularly morphology conservation is a basic requirement in membrane synthesis.…”
Section: Discussionmentioning
confidence: 88%
“…Systems with more than one soft segment forming polyol are much more common and known as bi‐soft segment or mixed soft segment PUs 7,9. In such systems, RIPS and their resulting morphologies are generally more complex but nevertheless frequently utilized to design, e.g., shape‐memory polymers10 or membranes11–14 with improved mechanical properties. Investigations on the influence of the morphology on final properties revealed that a precise control over morphology, i.e., microphase segregation, is mandatory to produce bi‐soft segment PUs with proper design 14,13,12,9.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tais observações podem ser interpretadas como um aumento nos graus de liberdade dos grupos uretano/uréia e da sua mistura com os grupos aromáticos e com o óxido de polipropileno [10,11]. A microscopia eletrônica de transmissão (TEM) [12]…”
Section: Elastômeros De Pu/pbdounclassified
“…A caracterização dos filmes por espectroscopia no infravermelho (IV) e análise térmica dinâmico-mecânica (DMTA) mostrou que o aumento da concentração de poli(butenodiol) (PBDO) enfraquece as pontes de hidrogênio entre os grupos uretano-uréia aumentando a mobilidade das cadeias e favorecendo a mistura com oóxido de 1 2 poli(propileno). Depois disso, a espectroscopia de reflexão total atenuada (ATR) e no infravermelho com transformada de Fourier (FTIR) [7] e a microscopia eletrônica de transmissão (TEM) [8] também foram usadas para confirmar o comportamento das separações de fases dos grupos flexíveis no elastômero.…”
Section: Capítulo 1 Introduçãounclassified